ANALISIS PELAKSANAAN PUTUSAN PENGADILANTERHADAP GUGATAN HARTA BERSAMA BERDASARKAN PUTUSAN NOMOR 1063/PDT.G/2022/PA.PTK - NIM. A1011201056, SYARIFAH NAJWA LUTFIAH (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The court serves as an institution designed to resolve disputes among members of society. It aids in safeguarding the intellectual property rights of conflicting parties. Court decisions are declaratory statements related to legal matters concerning disputes between parties over property or objects. Common property refers to assets acquired during the course of a marriage, from its inception to its termination. In contrast, individual property, known as